Application of a New Modified Nano Alumina as a Sorbent for Preconcentration and Determination of Cobalt ions in Food and Environmental Water Samples Prior to Flame Atomic Absorption Spectroscopy - Mirabi, A.; Fasamanesh, A. (Asian Journal of Chemistry, 2012)
The first study on the high efficiency of nanometer-sized g-alumina coated with sodium dodecyl sulfate-pyrrolidine dithiocarbamate (SDS-4-BPDC) as a new sorbent solid phase extraction has been reported. Sorbent with modified nanometer-sized alumina was used to preconcentrate and separate cobalt in food and environmental water samples. A microsample introduction system was employed for the nebulization micro-volume of diluted solution into flame atomic absorption spectroscopy. Various influencing parameters on the separation and preconcentration of trace metal, such as pH, amount of sorbent and concentration of the chelating agent, were studied. The calibration graph was linear in the range of 10-900 μg L-1 with detection limit of 3.1 μg L-1. The relative standard deviation (RSD) for ten replicate measurements was 2.2 %. The proposed method has been applied to the determination of cobalt at trace levels in real samples such as rice, tobacco, orange, green pepper, black tea, honey, potato, spinach, mangosteen, tomato, strawberry, carrot, apple, kiwi, mushroom, cucumber, lettuce, milk, wheat sprout, tab water, river water, sea water with satisfactory results.